Inactivation of the Tulane Virus, a Novel Surrogate for the Human Norovirus - TIAN, PENG (2013)
Human noroviruses (HuNoVs) are the major cause of nonbacterial gastroenteritis epidemics. The culturable feline calicivirus and murine norovirus have been used extensively as surrogates to study HuNoV biology, as HuNoV does not grow in vitro. Additional efforts to identify new surrogates are needed, because neither of these common surrogates are truly intestinal pathogens. The newly described Tulane virus (TV) is a typical calicivirus, it is isolated from macaque stools, is cultivable in vitro, and recognizes human histo-blood group antigens. Therefore, TV is a promising surrogate for HuNoVs. In this study, we evaluated the resistance or stability of TV under various physical and environmental conditions by measuring a 50% reduction of tissue culture infective dose (TCID(50)) by using a TV cell culture system. Due to the nature of this virus, it is hard to produce a high-titer stock through tissue culture. In our study, the maximal reduction in virus titers was 5 D (D = 1 log) in heat-denaturation and EtOH experiments, and 4 D in UV, chlorine, and pH-stability experiments. Therefore in this study, we defined the inactivation of TV as reaching a TCID50/ml of 0 (a 4- to 5-D reduction in TCID(50), depending on the detection limit). TV was inactivated after incubation at 63°C for 5 min, incubation at 56°C for 30 min (5 D), exposure to 60 mJ/cm(2) of UVC radiation (4 D), or incubation at 300 ppm of free chlorine for 10 min (4 D). TV was shown to be stable from pH 3.0 to 8.0, though an obvious reduction in virus titer was observed at pH 2.5 and 9.0, and was inactivated at pH 10.0 (4 D). TV was resistant to a low concentration of EtOH (40% or lower) but was fully inactivated (5 D) by 50 to 70% EtOH after a short exposure (20 s). In contrast, quantitative real-time PCR was unable to detect, or poorly detected, virus titer reductions between treated and untreated samples described in this study.